KESENJANGAN ANTARA NILAI PANCASILA DENGAN REALITAS ETIKA DALAM KONDISI POLITIK INDONESIA MASA KINI - Alfred Benu; Matilda Beatrix Klobong; Dina Sepriani Lasa; Priska Mariany Ratu Rihi; Roberta Yulianti Ndori; Novrinda Nadia Fahik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Pancasila is the foundation of the state, the national ideology, and the ethical guideline for national and state life. However, in contemporary Indonesian political practice, a significant gap remains between the ideal values ​​of Pancasila and the reality of political behavior. Phenomena such as corruption, money politics, polarization, hate speech, and abuse of power demonstrate the weak internalization of Pancasila values ​​within the political system. This article aims to analyze the forms of this gap, its causes, and its implications for the quality of Indonesian democracy. This research uses a qualitative approach through a literature review. The results indicate that the gap arises from a weak ethical political culture, inconsistent law enforcement, low elite role models, and the strengthening of pragmatic politics. Efforts to strengthen Pancasila political ethics need to be carried out through character education, political party reform, and just law enforcement.